Implementation and Operational Research: Implementation of Routine Counselor-Initiated Opt-Out HIV Testing on the Adult Medical Ward at Kamuzu Central Hospital, Lilongwe, Malawi. (1st May 2015) - LaCourse, Sylvia M.; Chester, Frances M.; Matoga, Mitch; Munthali, Charles; Nsona, Dominic; Haac, Bryce; Hoffman, Irving F.; Hosseinipour, Mina C.
Abstract : Abstract: The optimal approach of provider-initiated HIV testing and counseling (PITC) for inpatients in high-burden settings is unknown. We prospectively evaluated the implementation of task shifting from clinician-referral to counselor-initiated PITC on the medical wards of Kamuzu Central Hospital, Malawi. Most of patients (1905/3154, 60.4%) had an unknown admission HIV status. Counselors offered testing to 66.6% (1268/1905). HIV prevalence was 39.3%. Counselor-initiated PITC significantly increased HIV testing by 79% (643/2957 vs. 1228/3154), resulting in an almost 2-fold increase in patients with known HIV status (2447/3154 vs. 1249/3154) (both P < 0.0001), with 18.4% of those tested receiving a new diagnosis of HIV. Abstract : Supplemental Digital Content is Available in the Text.